Adopting a comprehensive quality strategy in service institutions - a field study at the port organization in Skikda - (Journal of Economic Additions, 2020)
The study aims to provide a theoretical framework on the subject of a comprehensive quality strategy, and to introduce the various concepts presented around it, while highlighting the most important strategies adopted, while conducting a field study at the level of the port of Skikda. The study found that there are varying levels in the application of the comprehensive quality strategy in the port of Skikda, where it was estimated after continuous improvement with weak, but after focusing on the customer and intensive training on the average.Keywords: Quality, Total Quality, Total Quality Strategy, Service Institutions.Jel Classification Codes: L30،M10، M19